Panava a senior synonym of Wulpisca, and description of new species of Panava and Dexosarcophaga (Bezzisca) from the Brazilian Amazon (Diptera, Sarcophagidae) - Da Silva Carvalho Filho, Fernando; Esposito, Maria Cristina (Zootaxa, 2011)
The generic name Wulpisca Lopes is placed as a junior synonym of a redefined Panava Dodge, a Neotropical taxon characterized by short apical spines on the male surstylus, a single phallotreme, presence of proclinate frontorbital bristles in the male, and setose wing vein R 1 . The species W. imbecilla (Wulp) and W. arnaudi Lopes are transferred to Panava and a new species, P. amazonica sp. nov., is described from Brazil. A key to males of the seven species of Panava is given. The subgenus Bezzisca Lopes of the predominantly Neotropical genus Dexosarcophaga Townsend comprises 17 species, including a new one described herein, D. (B.) tracua sp. nov. from Brazil. The key to species of D. (Bezzisca) by Silva and Mello-Patius (2010) is modified to include this new species.